1992
DOI: 10.1111/j.1365-2788.1992.tb00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against hepatitis B in preschool children with Down's syndrome

Abstract: Twenty-nine healthy HBsAg-and HBsAb-negative children with Down's syndrome who were living at home (mean age 42 months; 19 M, 10 F) were vaccinated against hepatitis B virus either with recombinant DNA or plasma-derived vaccine. Both groups of children responded well to the vaccination schedules, with HBsAb seroconversion rates close to 100%. Vaccination against hepatitis B in preschool children with Down's syndrome is effective in spite of the existing abnormalities of the immune function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…6 Predisposition to major hepatotropic viral infections and/or a diminished response to the hepatitis B vaccine also have been reported, but the evidence is questionable. [7][8][9][10] Hepatic steatosis is frequently described in association with Down syndrome, reportedly as an expected consequence of overweight and obesity, akin to other genetic conditions with mental retardation and a high body mass index (BMI), such as Prader-Willi syndrome. Valentini et al, reporting on 280 children and teenagers with Down syndrome, contribute to the discussion in this volume of The Journal.…”
mentioning
confidence: 99%
“…6 Predisposition to major hepatotropic viral infections and/or a diminished response to the hepatitis B vaccine also have been reported, but the evidence is questionable. [7][8][9][10] Hepatic steatosis is frequently described in association with Down syndrome, reportedly as an expected consequence of overweight and obesity, akin to other genetic conditions with mental retardation and a high body mass index (BMI), such as Prader-Willi syndrome. Valentini et al, reporting on 280 children and teenagers with Down syndrome, contribute to the discussion in this volume of The Journal.…”
mentioning
confidence: 99%
“…Numerosos estudios, iniciados en los años 1990, han mostrado que la vacunación induce en estos niños tasas de seroconversión del 93 al 100% 17,18 . Resultados que se alinean con los comunicados en adultos [19][20][21][22][23] y avalan el criterio de que la población Down no debe actualmente considerarse como un grupo especial al formular las estrategias vacunales frente a la hepatitis B 20 .…”
Section: Hepatitis Bunclassified
“…The World Health Organization (1992) has recommended that high-risk groups such as clients and staff of institutions for the mentally handicapped be vaccinated against hepatitis B. Vajro et al (1992) have demonstrated the effectiveness of vaccination against hepatitis B in preschool children with Down's syndrome. The potential for hepatitis B infection in non-residential settings suggests that clients and staff should be vaccinated against hepatitis B and those who intend using day-care facilities be vaccinated prior to entry into these programmes.…”
Section: Hbv Transmission In Familiesmentioning
confidence: 99%